What is more important than academic success? / Hazwati Hashim - Hashim, Hazwati (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
It has been well accepted that academics play a vital role in one's life. It can be seen when we structure our CV's, how many people state their academic qualifications first? How many have skills first? Commonly, the former always appears first rather than the latter. As much as academics is prioritized, we should not forget that there are other important skills that need to be instilled and acquired by today's generation. Here, we will probe the depth of social and emotional skills and the wisdom of academics. To begin with, social skills are vital for communication. Many students are- not fully aware of these skills particularly when they work with classmates for group work. Specifically, students need to be trained as to get along with others, to read social cues as to communicate effectively and to handle conflict resolution strategies whenever in disagreement situations. If students are not well-trained for these skills it will impede the pathway to success in their career. For instance, when they are at the workplace and will be surrounded with different kinds of behavior; these skills are crucial to successfully convey the message to other co- workers. This is also to avoid miscommunication in a case that others have misinterpreted the message. Additionally, during class instructions and assignments, learners are supposed to be taught on the organizational skills as such to start the task given immediately, manage time well, prepare a schedule and use effective study strategies to endure the challenges in study. Thus, this shows that students need to strengthen themselves with effective social skills.